Feeding Aspergillus oryzae Fermentation Culture (AOFC) to Growing Sheep: 1. The Effect of AOFC on Rumen Fermentation - Darwinsyah Lubis; Elizabeth Wina; Budi Haryanto; T Suhargiyantatmo (Jurnal Ilmu Ternak dan Veteriner, 2002)
Cultures of fungi, especially Aspergillus oryzae, have been of interest to animal nutritionists to increase feed efficiency. Many experiments have been done and showed positive results on rumen fermentation and productivity of ruminants. This paper reports the results of an in vivo study on feeding Aspergillus oryzae, fermentation culture (AOFC) to growing sheep. ‘Onggok’ (tapioca processing waste) was used as media for AO cultivation after being enriched with a mineral mixture. Commercial concentrate (GT-03) was fed to 15 growing sheep supplemented with 0% (C0), 5% (C1), and 10% (C2) AOFC (w/w). Chopped fresh King grass was used as a basal diet. The 3 treatments were randomly allotted to the sheep according to randomized block design with 5 replications. The study was carried out for 14 weeks. Digestion trial was conducted in the last 10 days of experiment. All feed and fecal samples were analyzed for nutrients. Rumen fluid was sampled at the mid experimental period. Analyses were done on rumen pH, ammonia content, (VFA) volatile fatly acids concentration, and also total digestive tract digestibility of dry and organic matter, crude protein, and total fiber (NDF). Differences in treatment means were analyzed by Duncan’s MRT. Feeding AOFC resulted in increased (P<0.05) digestibility of crude protein from 59.6% in control sheep to 65.5% in sheep fed concentrate with 10% AOFC supplementation. The same pattern also occurred for NDF, but no effect was found on dry and organic matter. Higher fiber digestibility with AOFC supplementation was in line with an increase (P<0.05) in cellulolytic bacteria population in the rumen. VFA produced also increased (P<0.05), as well as individual acids content, primarily acetate and propionate. No differences (P<0.05) were detected in rumen pH and ammonia content. It appears that AOFC is more suitable for the purpose of meat production.   Key words: A. oryzae, sheep, digestibility, rumen, in vivo